PENGUATAN GENDER DALAM PEMBELAJARAN HUMANIS - Munawarah Munawarah (Institut Agama Islam Negeri (IAIN) Bone-Indonesia, 2018)
Gender strengthening in the education process requires a structured effort that must begin by appreciating the inherent gender aspects of each community, both masculine and feminism. In this context, humanist education is an educational model that has a gender strengthening dimension.